Acidic Media Regulated Hierarchical Cobalt Compounds with Phosphorous Doping as Water Splitting Electrocatalysts. Issue 22 (24th April 2021) - Song, Danna; Sun, Jikai; Sun, Lanju; Zhai, Shengliang; Ho, Ghim Wei; Wu, Hao; Deng, Wei‐Qiao
Abstract: Facile synthesis of elaborate nanostructured transition metal compounds with tunable components remains challenging because multiple synthetic procedures or complex manipulation are normally involved. Herein, an acid‐etching strategy is applied to Co, in which the composition and morphology of the resultant materials are tunable. Specifically, a novel two‐tiered Co(CO3 )0.5 (OH)·0.11H2 O nanosheet is formed, part of which decomposes to produce hierarchical Co(CO3 )0.5 (OH)·0.11H2 O/Co3 O4 nanocomposite by tuning the etching condition. The composite shows bifunctional electrocatalytic capability towards the oxygen evolution and hydrogen evolution reactions (OER and HER). Moreover, the phosphorous dopant is introduced to boost the catalytic activity, especially in the HER. Density functional theory calculations reveal that the phosphorous dopant can dramatically push the binding energy to the ideal value, thus improving the HER performance. Computed results indicate that partial orbitals of the P atom are above the Fermi level and the P atom enhances the charge density of the neighboring Co atom, which optimizes the H* binding. In addition, an efficient overall water splitting configuration is performed with the integration of the P‐doped Co compound catalysts. The acid‐etching methodology inspires more novel nanostructured and multicomponent metal compounds for prominent electrocatalysis. Abstract : A morphology‐ and component‐tunable synthesis is applied to the acid‐etching of Co. The resultant hierarchical multicomponent nanocomposite exhibits bifunctional electrocatalytic activity for water electrolysis, which can be further improved by the implementation of phosphorous doping. An efficient full water splitting configuration is performed with the P‐doped Co species as the bifunctional electrocatalyst.